The Determination of the Relationship Social Stigma and Infertility Distress in Infertile Women - Yüksekol, Özlem Doğan; Yılmaz, Ayşe Nur; Baltacı, Nazlı; Ulucan, Mihriban (Ordu Üniversitesi, 2026)
Objective: This research was conducted to identify the relationship between social stigma and infertility distress in infertile women. Method: Designed as descriptive research, the study had a sample comprised of 166 infertile women applying in January-April 2022. Results: Means of participant women’s IDS and ISS scores were calculated respectively as 46.33±15.22 and 74.22±31.82 points. It was discerned that women’s IDS scores had statistically significant positive relationships with scores obtained by them from the ISS and its sub-scales (p

Amaç: Bu araştırma, infertil kadınlarda sosyal damgalanma ile infertiliteden etkilenme arasındaki ilişkiyi belirlemek amacıyla yapıldı. Yöntem: Tanımlayıcı tipte olan araştırmanın örneklemini Ocak- Nisan 2022 tarihleri arasında 166 infertil kadın oluşturdu. Bulgular: Araştırmaya katılan kadınların İEÖ puan ortalaması 46.33±15.22, İDÖ toplam puan ortalaması 74.22±31.82 olarak bulundu. Kadınların İEÖ ile İDÖ toplam puanları ve İDÖ alt boyutları arasında yüksek düzeylerde pozitif yönlü anlamlı bir ilişki belirlendi (p
İnfertil Kadınlarda Sosyal Damgalanma ile İnfertiliteden Etkilenme Arasındaki İlişkinin İncelenmesi
Keywords: Obstetrics and Gynocology Nursing; Doğum ve Kadın Hastalıkları Hemşireliği